PERLINDUNGAN KONSUMEN TERHADAP PRODUK KOSMETIK YANG TIDAK TERDAFTAR IZIN EDARNYA DI BPOM SEMARANG - Mufidatul Khasanah; Adi Suliantoro (Jurnal Ilmiah Dinamika Hukum, 2020)
The purpose of this study is to determine the protection of consumers who use cosmetics that are not registered with the BPOM, the legal consequences for cosmetic business actors who do not register their product distribution permits with BPOM and the solution. The research method used was normative juridical, with a descriptive analytical research specification. Obtaining data using secondary data through library research and interview techniques as a complement to secondary data which is then analyzed using descriptive qualitative methods. From the research results, it is concluded that the legal consequences for cosmetic business actors who do not register their product distribution permits with BPOM are administrative sanctions and criminal sanctions in accordance with Articles 45, articles 60 and 62 of the Consumer Protection Law Number 8 of 1999, Article 47 Paragraph (2) Regulation of the Food and Drug Supervisory Agency Number 12 of 2020, Article 20 of Minister of Health Regulation Number 1175 / Menkes / Per / XII / 2010 concerning Cosmetic Notifications, Articles 98, 106, 196 and 197, UUN Number 36 of 2009 concerning Health. The solution to this problem is that before distributing the cosmetic products it produces, business actors are required to register their products with BPOM in advance, so that there are no complaints, lawsuits and even criminal sanctions. Keywords: Consumer Protection, Cosmetics, Distribution license, BPOM